2013
DOI: 10.1371/journal.pone.0074352
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning Products, Environmental Awareness and Risk Perception in Mérida, Mexico

Abstract: Cleaning products are associated with many health and environmental problems. Contamination of water resources by cleaning products is more likely to occur with septic tanks as sewage treatment systems especially in karstic terrains. We explored women’s ideas about water sources and the risk cleaning products pose to health and sewage in Mérida, a city in the Yucatán peninsula of Mexico. Women were unaware of the city’s water management system. We found a positive and statistically significant association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
2
10
0
1
Order By: Relevance
“…Nineteen percent of the participants reported transferring cleaning or washing products to different containers, which might lead to mix‐ups with drinks or foods. Similar conclusions related to consumers’ behavior were drawn by other authors . Reasons for noncompliance with the safety instructions and hazard notes on cleaning and washing products might be manifold: nonattention to the information, low general risk perception, and intrapersonal factors (e.g., habitual or experiential factors, misconceptions, attitudes, and sociodemographics), as well as the products’ attributes, such as packaging, odor, or look .…”
Section: Theoretical Backgroundsupporting
confidence: 77%
“…Nineteen percent of the participants reported transferring cleaning or washing products to different containers, which might lead to mix‐ups with drinks or foods. Similar conclusions related to consumers’ behavior were drawn by other authors . Reasons for noncompliance with the safety instructions and hazard notes on cleaning and washing products might be manifold: nonattention to the information, low general risk perception, and intrapersonal factors (e.g., habitual or experiential factors, misconceptions, attitudes, and sociodemographics), as well as the products’ attributes, such as packaging, odor, or look .…”
Section: Theoretical Backgroundsupporting
confidence: 77%
“…Table 1 provides a brief description of the study. Survey participants were randomly chosen by a convenience sampling [40]. Demographic and education characteristics of the survey participants are presented in Table 2.…”
Section: Data Collection and Profile Of Respondentsmentioning
confidence: 99%
“…Lima et al [34] empirically showed that consumers' environmental awareness had an effect on product risk perception. Martínez-Peña [35] showed that the higher the environmental awareness measured with the knowledge about water resources and sewage management in a city was, the higher the risk perception for cleaning products was. Tseng et al [36] suggested that the higher the consumers' sensitivity to electromagnetic waves was, the higher the perception of health risks to mobile phones and household appliances became.…”
Section: Individual Propensity and Technology Acceptancementioning
confidence: 99%